Analisis Hukum Islam Terhadap Transaksi Jual Beli pada Platform Steam - Rahadian Rasyid Alyasa; Ganjar Eka Subakti (DPPM Universitas Pelita Bangsa, 2025)
This study examines the Islamic legal perspective on online game transactions through the Steam platform, focusing on aspects of ownership, content, legality, and benefits. The research method uses a qualitative approach based on literature studies that analyze secondary data from various sources. The results of the study show that Muhammadiyah, Nahdlatul Ulama (NU), and Persatuan Islam (Persis) have different but complementary views. Muhammadiyah emphasizes the importance of clarity of ownership and understanding of the terms of service, NU prioritizes transparency and moral supervision, while Persis is critical of the potential for losses due to limited property rights. These three organizations agree that transactions must be in accordance with sharia principles, the legality of the platform must comply with Islamic rules, and game content must reflect moral and religious values. In addition, Steam is considered to have positive educational and entertainment benefits if used wisely and supervised. This study provides a comprehensive understanding of the legality of transactions on digital platforms from an Islamic perspective.